Roles for Endothelial Cells in Dengue Virus Infection - Nadine A. Dalrymple; Erich R. Mackow (Advances in Virology)
Dengue viruses cause two severe diseases that alter vascular fluid barrier functions, dengue hemorrhagic fever (DHF) and dengue shock syndrome (DSS). The endothelium is the primary fluid barrier of the vasculature and ultimately the effects of dengue virus infection that cause capillary leakage impact endothelial cell (EC) barrier functions. The ability of dengue virus to infect the endothelium provides a direct means for dengue to alter capillary permeability, permit virus replication, and induce responses that recruit immune cells to the endothelium. Recent studies focused on dengue virus infection of primary ECs have demonstrated that ECs are efficiently infected, rapidly produce viral progeny, and elicit immune enhancing cytokine responses that may contribute to pathogenesis. Furthermore, infected ECs have also been implicated in enhancing viremia and immunopathogenesis within murine dengue disease models. Thus dengue-infected ECs have the potential to directly contribute to immune enhancement, capillary permeability, viremia, and immune targeting of the endothelium. These effects implicate responses of the infected endothelium in dengue pathogenesis and rationalize therapeutic targeting of the endothelium and EC responses as a means of reducing the severity of dengue virus disease.